Human Urinary Bladder Strip Relaxation by the β-Adrenoceptor Agonist Isoprenaline: Methodological Considerations and Effects of Gender and Age - Schneider, Tim; Fetscher, Charlotte; Michel, Martin C. (Frontiers in Pharmacology, 2011)
The present study was primarily designed to explore various methodological aspects related to organ bath experiments evaluating human detrusor relaxation by the β-adrenoceptor agonist isoprenaline. Data are based upon a series of 30 consecutive patients, and this cohort was also used to explore possible effects of gender and age. KCl-induced contraction was related to strip length but not weight or cross-sectional area, indicating that the former is most suitable for data normalization. Storage of detrusor strips in cold buffer for up to 2 days did not affect contractile responses to KCl or efficacy of isoprenaline to cause relaxation but significantly affected the isoprenaline potency. No such alterations were observed with up to 1 day of cold storage. The type (KCl vs. passive tension) or strength of contractile stimulus had only minor effects on isoprenaline responses although these differences reached statistical significance in some cases. Similarly, gender and age had only minor if any effects on KCl-induced contraction or isoprenaline-induced relaxation, but the current data are too limited for robust conclusions. In summary we have evaluated experimental conditions for the testing of human detrusor strip contraction and relaxation which should be useful for future larger studies.